2005
DOI: 10.1210/jc.2004-1337
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Differential Expression Analysis Reveals a New Set of Genes Involved in Thyroid Oncocytic Tumors

Abstract: Thyroid oncocytic adenomas are a class of tumors characterized by the presence of abundant mitochondria. We performed a differential display RT-PCR analysis on two oncocytic adenomas and their paired controls. We then carried out a microarray analysis using the 460 selected, differentially expressed clones on four other oncocytomas and their paired controls. Thirty genes, 12 encoded by mitochondrial DNA and 18 nuclear-encoded, were overexpressed by a factor of at least 2 in the tumors compared with the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 31 publications
2
73
0
Order By: Relevance
“…Using a two-step differential expression analysis of six Hürthle cell FTA and their paired normal tissues, Jacques et al (2005) found 30 overexpressed sequences in the tumoral tissues. Out of these 30 sequences, 12 were mtDNA encoded (ten genes from OXPHOS, the 16S rRNA gene and one noncoding sequence from D-Loop) and 18 nuclear encoded.…”
Section: Alterations In Gene Expression In Hü Rthle Cell Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a two-step differential expression analysis of six Hürthle cell FTA and their paired normal tissues, Jacques et al (2005) found 30 overexpressed sequences in the tumoral tissues. Out of these 30 sequences, 12 were mtDNA encoded (ten genes from OXPHOS, the 16S rRNA gene and one noncoding sequence from D-Loop) and 18 nuclear encoded.…”
Section: Alterations In Gene Expression In Hü Rthle Cell Tumorsmentioning
confidence: 99%
“…Hürthle cell tumors display a striking upregulation of mtDNA genes and of genes implicated in protein metabolism. The authors concluded that mitochondrial proliferation appears to be associated with intense protein turnover, suggesting that such turnover is necessary for the mitochondrial proliferation and/or that the mitochondrial saturation of the cytoplasm disturbs cell trafficking and processing of proteins (Jacques et al 2005). It would be interesting to compare these results with those obtained in non-Hürthle cell tumors to evaluate the specificity of the data.…”
Section: R136mentioning
confidence: 99%
“…Among these 126 genes, the Mitochondrial Ribosomal Protein Large subunit 49 (MRPL49) and 13 genes coding for subunits of the OXPHOS complexes were represented (Baris et al, 2004). A two-step study on the basis of differential display and macroarray analysis of six oncocytic thyroid adenoma samples showed that 12 of the 30 genes upregulated at least two-fold in the tumours were mtDNA-encoded genes (Jacques et al, 2005). Similarly to the data in renal and We used a public microarray data set (Giordano et al, 2006) containing data for 10 follicular thyroid adenomas (FTA), four NT, 15 oncocytic thyroid tumours (OTT) and 51 papillary thyroid carcinomas (PTC).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour samples (100) and normal conterparts (61) were used for tissue array construction, where each sample were represented by three spots (0.6 mm diameter); immunostaining was carried out using the standard avidin -biotin peroxidase technique as described earlier (Kononen et al, 1998;Jacques et al, 2005). The primary antibody was either a monoclonal anti-DAP3 (Transduction Laboratories, Lexington, UK; 1/50) or a monoclonal antibody against a mitochondrial subunit of the respiratory chain complex IV (clone 113-1, Biogenex laboratories, Inc., San Ramon, CA, USA; dilution 1/50).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…SENP1 mRNA levels are elevated in thyroid oncocytic adenocarcinoma (6) and human prostate cancer (PCa) 3 (10). In addition, using in situ hybridization, we recently found greater SENP1 mRNA levels in precancerous prostatic intraepithelial neoplasia (PIN) compared with adjacent normal prostate epithelia (10).…”
mentioning
confidence: 99%